2003
DOI: 10.1152/ajpregu.00199.2003
|View full text |Cite|
|
Sign up to set email alerts
|

μ-Opioid receptor agonist effects on medullary respiratory neurons in the cat: evidence for involvement in certain types of ventilatory disturbances

Abstract: Mu-opioid receptor agonists depress tidal volume, decrease chest wall compliance, and increase upper airway resistance. In this study, potential neuronal sites and mechanisms responsible for the disturbances were investigated, dose-response relationships were established, and it was determined whether general anesthesia plays a role. Effects of micro-opioid agonists on membrane properties and discharges of respiratory bulbospinal, vagal, and propriobulbar neurons and phrenic nerve activity were measured in pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 57 publications
(78 reference statements)
6
133
0
1
Order By: Relevance
“…Fentanyl, in doses of 20 -40 g/kg, was previously shown to consistently abolish membrane potential hyperpolarization and respiratory rhythmic phrenic nerve discharges, so that caudal expiratory neurons fire tonically during phrenic nerve apnea (16). In all three experiments of the present study, 30 g/kg doses of fentanyl produced tonic discharges (n ϭ 3 cells, one from each experiment; see Fig.…”
Section: R Agonist Administration Prevents Fentanyl Induction Of supporting
confidence: 62%
See 1 more Smart Citation
“…Fentanyl, in doses of 20 -40 g/kg, was previously shown to consistently abolish membrane potential hyperpolarization and respiratory rhythmic phrenic nerve discharges, so that caudal expiratory neurons fire tonically during phrenic nerve apnea (16). In all three experiments of the present study, 30 g/kg doses of fentanyl produced tonic discharges (n ϭ 3 cells, one from each experiment; see Fig.…”
Section: R Agonist Administration Prevents Fentanyl Induction Of supporting
confidence: 62%
“…Another issue investigated was whether or not D 1 R agonists alleviate opioid-evoked tonic discharges of caudal medullary expiratory neurons, an effect that was previously observed in pentobarbital-anesthetized and unanesthetized decerebrate cats (16), in chloralose-anesthetized dogs (18) and in motor nerve fibers that innervate the expiratory muscles of the chest wall in decerebrate rabbits (12). Because caudal medullary expiratory neurons provide excitatory synaptic drive to expiratory motoneurons (19), prevention of tonic discharges by D 1 R agonists would suggest effectiveness against chest wall rigidity caused by opiates…”
mentioning
confidence: 99%
“…A single preparation was employed to test the effects of each antitussive drug. Drug concentrations were in the same range as those previously used in in vivo preparations (4,13,19,21,22,35,50,56). All drugs were dissolved in 0.9% NaCl solution.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, we experienced a difficulty in mechanical ventilation via a face mask at the onset of apnea. It indicated that opioid-induced laryngeal closure might take some role in the respiratory arrest [16]- [19]. The aforementioned mechanisms are only speculative, and we are unable to propose explicit mechanisms that produced apnea in the patient.…”
Section: Discussionmentioning
confidence: 82%